Rumination’s Role in Second Victim Nurses’ Recovery From Psychological Trauma: A Cross-Sectional Study in China - Sun, Lianrong; Deng, Juan; Xu, Jixin; Ye, Xuchun (Frontiers in Psychology, 2022)
Background: Nurses can experience psychological trauma after adverse nursing events, making it likely for them to become second victims (SVs). This negatively impacts patient safety and nurses’ development. This study aims to understand the status of psychological trauma and recovery of nurses as SVs in domestic China and examine the influencing mechanism of cognitive rumination during their recovery from psychological damage. Methods: This was a cross-sectional survey. An online questionnaire was completed by 233 nurses from across China. Data were collected using Chinese versions of the Second Victim Experience and Support Evaluation Scale, the Incident-related Rumination Meditation Questionnaire, and the Post-traumatic Growth Rating Scale. Descriptive statistics, correlation, and regression, as well as mediation analysis, were used for different analyses in this study. Results: Participants experienced apparent psychological traumas (4.65±0.5583) with a certain degree of post-traumatic growth (76.18±16.0040); they reported a strong need for psychological support (95.7%). Psychological trauma was positively and negatively correlated with rumination and post-traumatic growth (r=.465, p<0.001; r=-.155, p<0.05) respectively. Both psychologically impaired experience and rumination had significant predictive effects on participants’ post-traumatic growth (both, p<0.001). Nurses’ active rumination significantly mediated their psychological recovery from trauma to post-traumatic growth (p<0.05), but the effect of invasive rumination was not significant (p>0.05). Limitation: The specific manifestations of the mechanism of invasive rumination are not clarified in this study. Conclusions: The present study investigated the psychological trauma of SV nurses as well as their support needs, and explored the role of cognitive rumination in the psychological repair and PTG of SV nurses. Results showed that SV nurses’ active rumination on adverse nursing events could promote their recovery from psychological trauma, but invasive rumination could not. This study provides a trauma-informed approach to care at the clinical level for nurses who experience psychological trauma caused by adverse events.